2021
DOI: 10.1177/15533506211007297
|View full text |Cite
|
Sign up to set email alerts
|

Technical Performance of Continuous Pressure Insufflators Versus Traditional Insufflators in the Presence of Leaks During Laparoscopic Surgery

Abstract: Background. New insufflators have been developed to manage leaks emanating from the working cavity during laparoscopic surgery. Little data have been published to show the performance of these insufflators. This study evaluates the performance of 2 modern continuous pressure insufflators in various leak conditions. Methods. Performance of a new continuous pressure insufflator, EVA15 (Palliare, Galway, Ireland), was compared with that of a continuous pressure insufflator, Airseal intelligent Flow System (iFS) (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…During this study, the total volume displacement was 30 mL at a simulated respiratory frequency of 15 breaths per minute. The diaphragm distortion in the model was similar to the pressure pattern described by Perretta et al [ 7 ]. The actual displacements used for the study are added as Supplementary file 1.…”
Section: Methodssupporting
confidence: 81%
See 1 more Smart Citation
“…During this study, the total volume displacement was 30 mL at a simulated respiratory frequency of 15 breaths per minute. The diaphragm distortion in the model was similar to the pressure pattern described by Perretta et al [ 7 ]. The actual displacements used for the study are added as Supplementary file 1.…”
Section: Methodssupporting
confidence: 81%
“…However, some controversy exists on the use of valveless trocar systems. Previous studies have shown that their use can lead to the entrainment of air [ 6 , 7 ] which might affect peritoneal pressure, humidity, carbon dioxide concentration, and temperature [ 8 ].…”
mentioning
confidence: 99%